Rare earth transition metal nitride magnetic powder
Patent Information
- Application Number
- CN202480090014.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2024-12-27
- Publication Date
- 2026-11-03
Smart Images

Figure CN123036167A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a rare earth transition metal nitrogen-based magnetic powder. Background Technology
[0002] Rare-earth transition metal nitrogen-based magnetic powders are alloy powders mainly composed of rare-earth metals, transition metals, and nitrogen. They are frequently used as materials for permanent magnets. For example, Sm₂Fe 17 N3-based alloy powders exhibit high saturation magnetization, anisotropic magnetic fields, and Curie temperatures. Therefore, they are useful as materials for permanent magnets, particularly bonded magnets, possessing excellent properties.
[0003] Rare earth transition metal nitrogen-based magnetic powders are typically manufactured by nitriding rare earth transition metal alloy powders. Previously known methods for manufacturing rare earth transition metal alloy powders include melt casting and reduction diffusion methods. The melt casting method uses rare earth metals and transition metals as raw materials, blends these materials, melts them in an inert gas environment, and then heat-treats the resulting alloy ingot to homogenize it before pulverizing it.
[0004] On the other hand, the reduction-diffusion method involves, for example, using rare earth oxides and transition metals as raw materials. These raw materials are mixed with a reducing agent such as metallic calcium, and then heated in a non-oxidizing gas environment to obtain a rare earth transition metal alloy. During the heating treatment, the rare earth oxides are reduced to rare earth metals, which diffuse into the transition metals to form an alloy (intermetallic compound). In the bulk reaction product obtained by the heating treatment, byproducts from the reducing agent remain along with the target alloy. Therefore, the reaction product is added to water to remove the byproducts from the reducing agent, and the reaction product is broken down and pulverized. The pulverized alloy powder is then subjected to acid washing and water washing to remove excess byproducts and unreacted substances, and further dried to obtain the target alloy powder.
[0005] The reduction-diffusion method can use inexpensive rare earth oxides and other raw materials, and the process is simple. Compared with the melting and casting method, it has the advantage of being able to manufacture alloy powders at low cost. Furthermore, by nitriding the alloy powder obtained by the reduction-diffusion method, rare earth transition metal alloy powders as nitrides can be obtained.
[0006] The master alloy used for nitriding is in powder form. To achieve uniform nitriding, a narrow particle size distribution of the master alloy powder is desirable. The reduction-diffusion method readily yields a narrow particle size distribution, thus becoming the mainstream method for manufacturing rare-earth transition metal nitrogen-based magnetic powders.
[0007] Examples of documents that disclose the manufacture of rare-earth transition metal nitrogen-based magnetic powders using a reduction-diffusion method include Patent Document 1 and Patent Document 2. These documents disclose the process of mixing rare-earth oxide powder, transition metal powder, and a reducing agent such as an alkali metal, heating the resulting mixture in an inactive environment, maintaining the resulting reaction product in a nitrogen environment, and performing a wet treatment on the resulting heat-treated product to manufacture rare-earth transition metal nitrogen-based alloy powders (claim 1 of Patent Document 1 and claim 1 of Patent Document 2).
[0008] Furthermore, it is known to form a phosphate protective film on the particle surface of magnetic powder to improve heat resistance and moisture resistance. For example, Patent Document 3 discloses the addition of phosphate during the pulverization of an iron-based magnetic alloy powder containing rare earth elements (claim 1 of Patent Document 3). Patent Document 4 discloses a method for manufacturing rare earth iron-nitrogen magnetic powder, which involves reducing, diffusing, and nitriding a raw material powder containing rare earth oxides to obtain an alloy block, immersing the alloy block in water to disintegrate it, followed by water washing and acid treatment. The method is characterized in that the acid treatment consists of treatment using a weak acid followed by treatment using an acid composed of group 5B elements and oxygen (claim 1 of Patent Document 4).
[0009] Existing technical documents
[0010] Patent documents
[0011] Patent Document 1: Japanese Patent Application Publication No. 05-148517.
[0012] Patent Document 2: Japanese Patent Application Publication No. 2007-119909.
[0013] Patent document 3: Japanese Patent Application Publication No. 2002-124406.
[0014] Patent document 4: Japanese Patent Application Publication No. 2000-038608. Summary of the Invention
[0015] The problem that the invention aims to solve
[0016] As mentioned above, a method for manufacturing rare-earth transition metal nitrogen-based magnetic powders using reduction diffusion has been proposed, in which a phosphate protective film is formed on the particle surface of the magnetic powder to improve moisture resistance. However, there is room for improvement in the prior art.
[0017] For example, Patent Documents 1 and 2 disclose methods for manufacturing rare-earth transition metal nitrogen-based magnetic powders, but the magnetic powders obtained by these methods exhibit deviations in maximum magnetic polarization. Therefore, it is difficult to consistently obtain the high maximum magnetic polarization inherent in the powder. Furthermore, while Patent Documents 3 and 4 disclose methods for forming a phosphoric acid protective film, the resulting protective film has poor uniformity, making it difficult to fully achieve the desired improvement in heat resistance.
[0018] The inventors conducted in-depth research in view of these problems. The results yielded the following insights: [The following appears to be a separate, unrelated sentence:] Containing at least rare earth metals (R), transition metals (TM), and nitrogen (N) as major components, and possessing Th₂Zn... 17 Type, Th2Ni 17 In rare earth transition metal nitrogen-based magnetic powders of any crystal structure, including TbCu7 type, the proportion of rare earth enriched phases is important. By controlling it, magnetic powders with stable high maximum magnetic polarization and excellent heat resistance can be obtained.
[0019] Furthermore, the following insights were obtained: In the manufacture of magnetic powders, in particular, the conditions of the reduction diffusion process, the nitriding process, and the wet processing process are important, and by controlling them, the aforementioned rare earth transition metal nitrogen-based magnetic powders can be easily manufactured.
[0020] This invention is based on the insight that aims to provide rare earth transition metal nitrogen-based magnetic powders with stable high maximum magnetic polarization and excellent heat resistance, as well as a method for manufacturing the same.
[0021] Methods for solving problems
[0022] The present invention includes the solutions described in (1) to (7) below. It should be noted that in this specification, the expression “~” includes the values at both ends. That is, “X~Y” is synonymous with “X and above and Y and below”. In addition, in this specification, as long as technical integration can be achieved, any combination of preferred methods can be adopted. For example, one of the preferred numerical ranges and the other can be combined arbitrarily.
[0023] (1) A method for manufacturing a rare earth transition metal nitrogen-based magnetic powder, wherein the rare earth transition metal nitrogen-based magnetic powder comprises at least a rare earth metal (R), a transition metal (TM), and nitrogen (N) as main components, and has Th2Zn 17 Type, Th2Ni 17 The rare earth transition metal nitrogen-based magnetic powder can be manufactured using any crystal structure of type TbCu7 or TbCu7, and the manufacturing method includes the following steps: The process of producing a reduction-diffusion treated material by heating a mixture of alloy raw materials containing at least rare earth metals (R), transition metals (TM) and oxygen (O) and a reducing agent in a depressurized gas or inactive gas environment to a temperature of 800°C or higher and 1200°C or lower (reduction-diffusion process). The process of exposing the aforementioned reduction and diffusion treated material to a hydrogen environment for crushing, thereby producing crushed material (hydrogen crushing process). The process of producing nitrides by nitriding the aforementioned crushed materials (nitriding process); and The process of producing a wet-treated product by performing wet treatment on the aforementioned nitrides (wet treatment process). The average atomic ratio (R / TM ratio) of rare earth metals (R) to transition metals (TM) in the aforementioned raw material mixture is above 0.117 and below 0.160. During the aforementioned nitriding treatment, the pressure of the surrounding environment of the crushed material is reduced to below 50 kPa, and then the pressure is restored using a hydrogen-free nitriding gas. This operation is performed at least once. Then, a hydrogen-containing nitriding gas is supplied to the surrounding environment, and the crushed material is heated in the supplied nitriding gas environment to transform it into a nitride. The aforementioned wet processing steps include: a sub-step (first water washing step) of adding the aforementioned nitride to water and causing it to disintegrate to produce a slurry containing nitride particles; a sub-step (acid washing step) of performing water washing on the slurry containing the aforementioned nitride particles after the first water washing step; a sub-step (second water washing step) of performing water washing on the slurry containing nitride particles after the acid washing step; a sub-step (surface treatment step) of adding an aqueous phosphoric acid solution to the slurry containing nitride particles after the second water washing step to form a phosphorus-containing protective film on the surface of the aforementioned nitride particles; and a sub-step (third water washing step) of performing water washing on the slurry containing nitride particles after the surface treatment step to obtain the aforementioned wet-processed product. In the aforementioned rare earth transition metal nitrogen-based magnetic powder, the average atomic ratio (R / TM ratio) of rare earth metal (R) to transition metal (TM) is above 0.107 and below 0.121.
[0024] (2) According to the method of (1) above, wherein in the aforementioned pickling process, the temperature of the slurry containing nitride particles is maintained above 13°C and below 30°C.
[0025] (3) According to the method of (1) or (2) above, wherein, in the aforementioned surface treatment process, the concentration of transition metal (TM) in the supernatant of the slurry containing nitride particles before being added to the phosphoric acid aqueous solution is less than 1.0 g / L.
[0026] (4) The method according to any one of (1) to (3) above, wherein the amount of the phosphoric acid aqueous solution added in the aforementioned surface treatment process is more than 0.03% by mass and less than 1.0% by mass relative to the aforementioned rare earth transition metal nitrogen-based magnetic powder in terms of phosphorus (P).
[0027] (5) The method according to any one of (1) to (4) above, wherein in the aforementioned surface treatment process, the temperature of the slurry containing nitride particles is maintained at 13°C or higher and 30°C or lower.
[0028] (6) According to any one of (1) to (5) above, wherein in the aforementioned third water washing process, water washing treatment is performed until the phosphorus (P) concentration of the supernatant of the slurry is below 100 mg / L.
[0029] (7) A rare earth transition metal nitrogen-based magnetic powder, comprising at least rare earth metals (R), transition metals (TM), and nitrogen (N) as main components, having Th2Zn 17 Type, Th2Ni 17 Any crystal structure in the TbCu7 type and TbCu7 type, wherein, In the aforementioned rare-earth transition metal nitrogen-based magnetic powders, the average atomic ratio (R / TM ratio) of rare-earth metals (R) to transition metals (TM) is between 0.107 and 0.121, and the area proportion of rare-earth enriched phases with an R / TM ratio exceeding 0.130 is less than 1.0%. When heated at 150°C for 1000 hours in the atmosphere, the coercivity retention rate [HcJ(1000) / HcJ(0)], which is the ratio of the coercivity after heating (HcJ(1000)) to the coercivity before heating (HcJ(0)), is over 83%.
[0030] The effects of the invention
[0031] According to the present invention, a rare earth transition metal nitrogen-based magnetic powder with stable high maximum magnetic polarization and excellent heat resistance is provided, as well as a method for manufacturing the same. Attached Figure Description
[0032] Figure 1 The image shown is a scanning electron microscope (SEM) image (reflected electron image) of magnetic powder (Example 1).
[0033] Figure 2 An SEM image (reflected electron image) of magnetic powder is shown (Example 7).
[0034] Figure 3The results of thermogravimetric (TG) determination of magnetic powders are shown (Examples 1 and 8). Detailed Implementation
[0035] Hereinafter, specific embodiments of the present invention (hereinafter referred to as "this embodiment") will be described. However, the present invention is not limited to the following embodiments, and various modifications can be made without changing the spirit of the present invention.
[0036] 1. Manufacturing method of rare earth transition metal nitrogen-based magnetic powder
[0037] This embodiment relates to a method for manufacturing rare-earth transition metal nitrogen-based magnetic powder (hereinafter, sometimes simply referred to as "magnetic powder"). The magnetic powder contains at least a rare-earth metal (R), a transition metal (TM), and nitrogen (N) as its main components, and has a Th₂Zn composition. 17 Type, Th2Ni 17 The magnetic powder can have any crystal structure, including the TbCu7 type. Furthermore, the average atomic ratio (R / TM ratio) of rare earth metals (R) to transition metals (TM) in this magnetic powder is between 0.107 and 0.121.
[0038] The manufacturing method of this embodiment includes the following steps: a step of heating a raw material mixture containing at least rare earth metals (R), transition metals (TM), and oxygen (O) and a reducing agent to a temperature of 800°C or higher and 1200°C or lower in a reduced pressure gas or inactive gas environment to produce a reduction-diffusion treated product (reduction-diffusion step); a step of exposing the reduction-diffusion treated product to a hydrogen environment for crushing to produce a crushed product (hydrogen crushing step); a step of performing nitriding treatment on the crushed product to produce a nitride (nitriding step); and a step of performing wet treatment on the nitride to produce a wet treated product (wet treatment step). Here, the average value of the atomic ratio (R / TM ratio) of the rare earth metals (R) to the transition metals (TM) contained in the raw material mixture is 0.117 or higher and 0.160 or lower. In addition, during nitriding, the pressure of the surrounding environment of the crushed material is reduced to below 50 kPa, and the pressure is restored using nitriding gas that does not contain hydrogen. This operation is performed at least once. Then, nitriding gas that can contain hydrogen is supplied to the surrounding environment, and the crushed material is heated in the supplied nitriding gas environment to transform it into nitride.
[0039] Furthermore, the wet processing steps include: a sub-step of adding nitrides to water and causing them to disintegrate to produce a slurry containing nitride particles; a sub-step of performing water washing on the slurry containing nitride particles (first water washing step); a sub-step of performing acid washing on the slurry containing nitride particles after the first water washing step (acid washing step); a sub-step of performing water washing on the slurry containing nitride particles after the acid washing step (second water washing step); a sub-step of adding an aqueous phosphoric acid solution to the slurry containing nitride particles after the second water washing step to form a phosphorus-containing protective film on the surface of the nitride particles (surface treatment step); and a sub-step of performing water washing on the slurry containing nitride particles after the surface treatment step to obtain the wet-treated product (third water washing step). Each step is described in detail below.
[0040] <Reduction and Diffusion Process>
[0041] In the reduction-diffusion process, a mixture of raw materials containing at least rare earth metals (R), transition metals (TM), and oxygen (O) and a reducing agent is prepared. The alloy raw materials only need to contain at least rare earth metals, transition metals, and oxygen as constituent elements. During the reduction-diffusion treatment, oxygen is removed from the alloy raw materials by the action of the reducing agent, and simultaneously, the rare earth metals diffuse into the transition metals, thus alloying. This yields a reduction-diffusion treated product (reaction product) containing a rare earth transition metal alloy and byproducts from the reducing agent.
[0042] [In the case of alloy raw materials - powder mixtures]
[0043] The alloy raw material can be a powder mixture, namely a mixture of rare earth oxide powder and transition metal powder. The rare earth oxide powder is the raw material for the rare earth metal constituting the target magnetic powder. The type of rare earth metal is selected according to the composition of the target magnetic powder. Although not limited, examples of rare earth metals include one or more selected from the group consisting of yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), and ytterbium (Yb). The rare earth oxide powder can be used alone, or two or more powders can be used in combination.
[0044] Rare earth metals preferably include samarium (Sm). By selecting Sm, samarium iron nitrogen (Sm2Fe) can be produced. 17 N3) is a magnetic powder. Sm2Fe 17N3-based magnetic powders possess excellent magnetic properties, making them useful as bonding magnet materials. Additionally, in this case, Sm can be combined with other rare earth metals besides Sm, such as La and / or Ce. For example, Sm can be composed of 70% or more of the rare earth metals, while other elements (La, Ce, etc.) can be used for the remaining 30% or less.
[0045] The particle size of the rare earth oxide powder can be determined based on the composition and intended use of the resulting alloy powder. However, it is preferable to determine the particle size of the rare earth oxide powder in a manner that ensures a uniform distribution of the rare earth oxide powder near the transition metal particles in the resulting mixture. The average particle size D50 of the rare earth oxide powder is preferably 50 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. Particularly preferred is a powder in which particles with a particle size of 0.1 to 10 μm account for 80% or more of the total mass. This improves the mixability of the raw materials and the operability of the raw material powder and reaction products. Furthermore, it allows for sufficient diffusion of rare earth metals in subsequent reduction diffusion processes. It should be noted that, in this specification, the average particle size D50 refers to the cumulative 50% diameter in the particle size distribution based on volume. The particle size distribution based on volume can be determined using an airflow dispersion type laser diffraction particle size distribution measuring device.
[0046] Rare earth oxide powders sometimes contain moisture and organic matter as impurities. These impurities can sometimes increase the oxygen content of the final alloy powder. Therefore, it is preferable that the rare earth oxide powder contains a low amount of impurities. For example, the loss on heating after heating to 1000°C is preferably 2% by mass or less, more preferably 1% by mass or less.
[0047] Transition metal powder is the raw material for the transition metal that constitutes the target magnetic powder. The type of transition metal can be selected according to the composition of the target magnetic powder. Although not limited, examples include one or more selected from the group consisting of iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), chromium (Cr), manganese (Mn), zinc (Zn), molybdenum (Mo), and tungsten (W). As transition metal powder, a single powder can be used, or two or more powders can be used in combination.
[0048] The transition metal preferably includes iron (Fe). By selecting Fe, samarium iron nitrogen (Sm2Fe) can be produced. 17N3)-based magnetic powder. In this case, Fe can also be combined with other transition metals besides Fe, for example, one or more selected from the group consisting of Cr, Mn, Co, and Ni. For example, 90 atomic percent or more of the transition metal can be Fe, and less than 10 atomic percent can be composed of other elements (Cr, Mn, Co, Ni, etc.). When the transition metal powder is iron (Fe), cobalt (Co), nickel, or (Ni) powder, for example, reducing powder, gas atomized powder, water atomized powder, electrolytic powder, carbonyl powder, etc. can be used.
[0049] As transition metal powder, only metal powder can be used, or a portion of it can be replaced with metal oxide powder. Furthermore, not only transition metals can be used, but also substances containing other metals, such as rare earth metals. For example, as transition metal powder, metal powder (Fe, etc.), metal oxide powder (Fe₂O₃, Fe₃O₄, FeO, etc.), and rare earth transition metal alloy powder (R₂Fe) can be used. 17 Examples of suitable materials include rare earth transition metal composite oxide powders (such as RFeO3). However, if oxide powders are used, an aluminothermic reaction occurs during the reduction diffusion process. From the viewpoint of suppressing the rapid exothermic reaction caused by this reaction, it is preferable to keep the proportion of oxide powder in the overall transition metal powder to below 50% by mass.
[0050] When the transition metal powder is a metal powder, considering the diffusion length of rare earth metals at the reduction diffusion treatment temperature, the average particle size D50 of the transition metal powder is preferably 100 μm or less, more preferably 50 μm or less. On the other hand, when the transition metal powder is an oxide powder, the D50 of the transition metal powder is preferably 10 μm or less, more preferably 5 μm or less.
[0051] [Case other than alloy raw materials - powder mixtures]
[0052] The alloying raw material can be an oxide and / or partially reduced oxide (partial oxide) containing rare earth metals and transition metals; an alloy containing rare earth metals, transition metals, and oxygen (e.g., an oxygen-containing SmFe alloy); or a mixture containing rare earth metals, transition metals, and rare earth oxides (e.g., a mixture of SmFe alloy and Sm oxide). By using partially reduced oxides as the alloying raw material, the amount of reducing agent added in subsequent processes can be suppressed. The following is an example of the preparation steps for a partially reduced oxide containing rare earth metals and transition metals.
[0053] First, a composite oxide containing rare earth metals (Re) and transition metals (TM) is prepared. The method for obtaining the composite oxide is not limited. For example, the composite oxide can be synthesized via a wet process. In the wet process, a hydroxide is generated from an acid solution containing rare earth metals and transition metals through a neutralization reaction, and the resulting hydroxide is then heat-treated. Then, the prepared composite oxide is heated in a reducing environment to obtain a partially reduced oxide containing rare earth metals and transition metals.
[0054] [reducing agent]
[0055] The reducing agent is added to promote alloy formation by reducing oxide components such as rare earth oxide powders during subsequent reduction-diffusion treatment. At least one reducing agent selected from alkali metals, alkaline earth metals, and their hydrides is used. Specifically, one or more selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and their hydrides are preferred. From the viewpoint of safety and cost during processing, Li and / or Ca are more preferred, and Ca is particularly preferred.
[0056] The reducing agent is preferably in granular form. Increasing the coarseness of the reducing agent promotes its penetration and diffusion into the raw material mixture after it has been heated to a molten state during the reduction diffusion treatment. The particle size of the reducing agent is preferably 100 mesh or more (coarser than 100 mesh sieve material), more preferably 32 mesh or more. On the other hand, if the reducing agent is fine, its dispersibility in the raw material mixture can be further improved. The particle size of the reducing agent is preferably 4 mesh or less (fineer than 4 mesh sieve material), more preferably 9 mesh or less.
[0057] [Other ingredients]
[0058] Depending on the requirements, other components besides rare earth oxide powders, transition metal powders, and reducing agents may be added. For example, when manufacturing magnetic powders containing components other than rare earth metals, transition metals, and nitrogen, other raw materials may also be added. Examples of such components include zinc (Zn), boron (B), aluminum (Al), gallium (Ga), indium (C), silicon (Si), germanium (Ge), tin (Sn), lead (Pb), and / or bismuth (Bi).
[0059] [mix]
[0060] The raw materials can be mixed using known methods, either wet or dry. For dry mixing, any dry mixer such as a belt mixer, tilting mixer, S-type mixer, V-type mixer, Nauta mixer, Henschel mixer, Miralo mixer, Nobilta mixer, mechanical blender, high-speed mixer, and / or vibratory mill can be used. For wet mixing, water or an organic solvent is used as the mixing medium, and the raw materials are mixed using a wet mixer such as a ball mill and / or bead mill, followed by drying. However, in wet mixing, it is preferable to wet mix the raw materials other than the reducing agent (such as metallic Ca), and then add the reducing agent.
[0061] In the manufacturing method of this embodiment, the average value of the atomic ratio (R / TM ratio) of rare earth metals (R) to transition metals (TM) in the raw material mixture is 0.117 or higher and 0.160 or lower. This suppresses the formation of heterogeneous phases and yields magnetic powder with excellent magnetic properties. Conversely, when the average value of the R / TM ratio is less than 0.117, the diffusion of rare earth metals during the reduction-diffusion treatment may become insufficient. Therefore, the reaction product after the reduction-diffusion treatment (reduction-diffusion treated product) may contain insufficient amounts of transition metal-enriched phases (such as iron-enriched phases), which may reduce the magnetic properties of the magnetic powder, such as residual magnetic flux density or rectangularity. When the average value of the R / TM ratio exceeds 0.160, the amount of rare earth-enriched phases as heterogeneous phases increases, and the proportion of the main phase decreases. Therefore, the magnetic properties of the magnetic powder, such as residual magnetic flux density or rectangularity, may decrease. The average value of the R / TM ratio is more preferably 0.123 or higher and 0.135 or lower. It should be noted that the average R / TM ratio of the raw material mixture is calculated from the proportions of rare earth metal (R) raw materials and transition metal (TM) raw materials added during the preparation of the raw material mixture.
[0062] The amount of reducing agent contained in the raw material mixture is preferably 1.05 equivalents or more and 3.0 equivalents or less, more preferably 1.1 equivalents or more and 2.0 equivalents or less. Here, equivalent is an indicator of the amount required to reduce the oxides contained in the raw material mixture. The minimum amount required to reduce all oxides is defined as 1 equivalent. By setting the reducing agent dosage to 1.05 equivalents or more, the oxides can be sufficiently reduced. On the other hand, if there is too much reducing agent, the excess component of the reducing agent remains, which may sometimes hinder nitriding in the subsequent nitriding process. By setting the reducing agent dosage to 3.0 equivalents or less, nitriding hindrance in the nitriding process can be prevented.
[0063] In the reduction-diffusion process, a prepared raw material mixture is heated under reduced pressure or an inert gas environment to produce a reduction-diffusion treated product. During the reduction-diffusion process, rare earth oxides are reduced to rare earth metals by the action of a reducing agent (such as metal Ca). The generated rare earth metals diffuse into transition metals to form rare earth transition metal alloys. Therefore, the reduction-diffusion treated product contains a rare earth transition metal alloy as the main phase and byproducts from the reducing agent (such as CaO), and may contain other heterogeneous phases depending on the situation.
[0064] During heating, the raw material mixture is filled into an iron reaction vessel, heated to the specified temperature, held for a predetermined time, and then cooled. The heating temperature is set between 800°C and 1200°C. When the heating temperature is below 800°C, the reduction reaction of the reducing agent on the oxides is insufficient. When the heating temperature exceeds 1200°C, the sintering of alloy particles in the reaction product (reduction-diffusion treated product) generated by the reduction-diffusion reaction occurs, and the diffusion of nitrogen in the subsequent nitriding process may not proceed smoothly. Alternatively, in wet processing, there is also the problem of difficulty in slurry formation, resulting in the residue of coarse lumps. The temperature and holding time are preferably determined in a way that allows rare earth metals to diffuse to the center of the iron particles in the raw material mixture, without leaving a transition metal enriched phase. It should be noted that, in order to reduce residual gases such as oxygen and moisture in the reaction vessel, the vessel can be evacuated and replaced with an inactive gas before or during heating. In addition, it is preferable to maintain an inactive gas environment during cooling to prevent oxidation of the reaction products and maintain their activity.
[0065] <Hydrogen Crushing Process>
[0066] In the hydrogen crushing process, the reduction-diffusion treated material obtained in the reduction-diffusion process is exposed to a hydrogen environment for crushing, thereby producing crushed material. The reaction product obtained through reduction-diffusion treatment (reduction-diffusion treated material) contains rare earth-enriched phases that excessively contain rare earth elements. For example, in the case where the rare earth metal is Sm, it contains Sm-enriched phases such as SmFe5, SmFe3, and / or SmFe2. If the reduction-diffusion treated material is exposed to a hydrogen environment, these rare earth-enriched phases absorb hydrogen and expand in volume. Therefore, cracks are generated in the reduction-diffusion treated material, enabling it to be crushed. The size of the crushed material is not limited, for example, it can be less than 10 mm. In the case of large crushed materials, mechanical crushing can be performed.
[0067] <Nitriding process>
[0068] In the nitriding process, the crushed material obtained in the hydrogen crushing process is nitrided to produce nitrides. Through nitriding, the rare earth transition metal alloys contained in the crushed material are nitrided to generate rare earth transition metal nitrogen compounds.
[0069] During nitriding, firstly, as a pretreatment, the pressure around the crushed material is reduced to below 50 kPa, and then the pressure is restored using a hydrogen-free pretreatment gas. This operation is performed at least once. The reaction product (crushed material) after the hydrogen crushing process is typically a blocky, porous sintered body, with residual hydrogen in its pores and cracks. The inventors conducted research and realized that if hydrogen remains, it may hinder the diffusion of nitrogen through the pores and cracks. Therefore, by performing pretreatment using a hydrogen-free gas (pretreatment gas), residual hydrogen can be removed, resulting in uniform and thorough nitriding.
[0070] If the ambient pressure after depressurization exceeds 50 kPa, hydrogen removal becomes insufficient, and nitriding may become uneven and incomplete. As the pretreatment gas introduced during pressure recovery, it is preferable to use nitrogen-containing gases (nitriding gases) such as nitrogen that do not contain hydrogen and / or ammonia. If the pretreatment gas (nitriding gas) contains hydrogen, hydrogen that hinders nitriding may remain in pores and cracks after pretreatment. Furthermore, the pretreatment process should be performed at least once, preferably twice or more.
[0071] After pretreatment, a nitriding gas containing hydrogen (a nitrogen-containing gas) is supplied to the surrounding environment, and the crushed material is heated in the supplied nitriding gas environment to transform it into a nitride. The supplied nitriding gas may or may not contain hydrogen. As the nitriding gas, a nitrogen-containing gas such as nitrogen and / or ammonia is preferred. Furthermore, to control the nitriding reaction rate, other gases such as hydrogen, argon, and helium may be included in the nitrogen-containing gas (nitriding gas). For example, a mixture of ammonia and hydrogen can sufficiently nitride into the interior of large alloy particles with a particle size exceeding 10 μm. In this case, the nitrogen (N) content of the final magnetic powder can be increased to 2.5% by mass or more and 5.0% by mass or less. When a mixture of ammonia and hydrogen is used as the nitriding gas, the pressure ratio of ammonia to the total pressure (ammonia partial pressure) is preferably 0.20 or more and 1.00 or less, more preferably 0.30 or more and 0.95 or less. By setting the ammonia partial pressure to 0.20 or more, the nitriding of the alloy particles is further promoted. In addition, the amount of nitrogen gas supplied cannot be fixed in general, but in order to make the amount of N in the magnetic powder sufficiently high, it is preferable to adjust it to, for example, 2.5% by mass or more and 5.0% by mass or less.
[0072] The heating temperature (nitriding temperature) of the crushed material is preferably 350°C or higher and 500°C or lower, more preferably 400°C or higher and 480°C or lower. By setting the heating temperature to 350°C or higher, nitrogen can be rapidly diffused into the interior of the alloy particles. On the other hand, if the heating temperature is too high, the alloy may decompose. For example, in the case where the transition metal is Fe, the alloy sometimes decomposes to form heterogeneous phases of α-Fe and Fe nitrides, which degrade the magnetic properties of the magnetic powder. By setting the heating temperature to 500°C or lower, the formation of such heterogeneous phases can be suppressed. In addition, the optimal heating time varies depending on various conditions such as heating temperature and throughput. Therefore, it is difficult to determine the heating time uniquely. In order to sufficiently increase the N content in the magnetic powder, it is preferably adjusted to 2.5% by mass or higher and 5.0% by mass or lower, for example.
[0073] Preferably, the nitride after nitriding is subjected to heat treatment under hydrogen gas, an inert gas, or a reduced pressure gas. Examples of inert gases include nitrogen, argon, and / or helium. More preferably, heat treatment is performed under nitrogen and / or argon gas after heat treatment with hydrogen. By performing heat treatment after nitriding, the uniformity of nitrogen distribution in the nitride can be achieved to a higher level. However, this heat treatment is not an essential step. The magnetic powder of this embodiment can be obtained even without performing heat treatment after nitriding.
[0074] <Wet Processing Procedure>
[0075] In the wet processing step, nitrides are subjected to wet treatment to produce a wet-treated product. The nitrides obtained in the nitriding process are typically bulk porous bodies. More specifically, they are condensates formed by the bonding of nitride particles, which serve as the main phase. It should be noted that nitride particles refer to particles of rare-earth transition metal nitrogen compounds. In addition to nitride particles, nitrides also contain byproducts from the reducing agent (such as CaO) and heterogeneous phases (such as rare-earth enriched phases). Through wet processing, the bonds between the nitride particles are broken, resulting in a magnetic powder composed of rare-earth transition metal nitrogen compounds. Furthermore, wet processing can remove byproducts and heterogeneous phases other than the main phase, and can form a heat-resistant protective coating on the surface of the nitride particles. The wet processing step includes a first water washing step, an acid washing step, a second water washing step, a surface treatment step, and a third water washing step as sub-steps.
[0076] [First washing process]
[0077] In the wet processing step, firstly, the nitride is added to water and allowed to disintegrate, creating a slurry containing nitride particles. Then, the slurry containing the nitride particles is subjected to a water washing process (first water washing step). Slurry preparation simply involves adding the nitride to water. Upon addition to water, byproducts from the reducing agent (calcium oxide, calcium nitride, etc.) contained in the nitride become calcium hydroxide. Simultaneously, the nitride disintegrates, yielding a suspension (slurry) containing nitride particles and calcium hydroxide particles as insoluble water components.
[0078] Furthermore, the method of water washing is not limited. For example, a series of operations including stirring, settling, and decantation can be performed on slurries containing nitrides. Water can also be added to the slurry as needed. Byproducts (such as CaO) from the reducing agent contained in the nitrides are transformed into hydroxides (such as Ca(OH)2) in the slurry. These hydroxides have a different specific gravity than the nitride particles. Therefore, by decantation, the supernatant of the slurry and the hydroxides from the reducing agent can be removed together. From the viewpoint of obtaining nitride particles of high purity, it is preferable to repeat this series of operations. It should be noted that the supernatant refers to the liquid at the top of the slurry after the slurry has been settling due to the higher specific gravity of the nitride particles. The supernatant can also be called the clear liquid. However, sometimes components with a lower specific gravity than the nitride particles, such as hydroxides, are suspended in the supernatant (clear liquid). Therefore, the supernatant is not necessarily transparent.
[0079] The concentration, temperature, and number of decantations of the slurry in the first washing step are not limited. However, it is preferable that the concentration of the reducing agent component in the slurry at the end of the first washing step is low. For example, when using calcium (Ca) as a reducing agent, the Ca concentration in the supernatant obtained after water washing and allowing the slurry to stand is preferably 1.0 g / L or less, more preferably 0.1 g / L or less. In this case, the supernatant exhibits an alkaline pH of 8 to 13. The acid added in the subsequent acid washing step first neutralizes the slurry and is consumed in a manner that lowers the pH to below 7, and then is consumed to dissolve byproducts and heterogeneous phases. When there is a deviation in the concentration of the reducing agent component (Ca, etc.) in the slurry at the end of the first washing step, the amount of byproducts and heterogeneous phases dissolved will be different, which may induce deviations in the magnetic properties of the final magnetic powder. By keeping the concentration of the reducing agent component in the slurry low, magnetic powder with high purity and excellent magnetic properties can be obtained stably.
[0080] [Pickling process]
[0081] Next, the slurry containing nitride particles obtained in the first water washing process is subjected to acid washing treatment (acid washing process). Even if byproducts from the reducing agent (such as Ca(OH)2) and heterogeneous phases (such as rare earth enriched phases) remain in the nitride particles, they can be removed by acid washing.
[0082] In acid cleaning, acid is simply added to the slurry containing nitride particles. It is preferable to ensure uniform contact between the nitride particles and the acid in the slurry, therefore stirring the slurry is preferred. The acid is not particularly limited as long as it can dissolve and remove byproducts (such as Ca(OH)₂) and heterogeneous phases (such as rare earth enriched phases). However, at least one selected from the group consisting of acetic acid, hydrochloric acid, and nitric acid is preferred.
[0083] The amount of acid added is adjusted so that the average atomic ratio (R / TM ratio) of rare earth metals (R) to transition metals (TM) in the final magnetic powder is between 0.107 and 0.121. By adjusting the amount of acid added, magnetic powders with superior magnetic properties can be produced. Conversely, if the average R / TM ratio is less than 0.107, a larger amount of acid is added, resulting in excessively strong acid cleaning. This produces strong etching marks on the surface of the particles constituting the powder, and magnetic properties sensitive to the particle surface structure, such as coercivity, may decrease. On the other hand, if the amount of acid added is so small that the average R / TM ratio exceeds approximately 0.121, the acid cleaning effect cannot be sufficiently obtained. Due to the presence of residual byproducts and heterogeneous phases, the magnetic properties of the magnetic powder, such as maximum magnetic polarization, may decrease.
[0084] Preferably, during the pickling process, the temperature of the slurry containing nitride particles is maintained between 13°C and 30°C. By adjusting the slurry temperature, magnetic powders with superior magnetic properties can be produced. Conversely, when the slurry temperature is below 13°C, the pickling effect cannot be fully achieved. Due to the presence of residual byproducts and heterogeneous phases, the magnetic properties of the magnetic powder, such as maximum magnetic polarization, are reduced. When the slurry temperature exceeds 30°C, even if the average R / TM ratio is in the range of 0.107 to 0.121, excessive amounts of rare earth ions and iron ions will dissolve from the slurry, which will contaminate the surface of the nitride particles. If the nitride particle surface is contaminated, the formation of a protective film in subsequent surface treatment processes is hindered. Therefore, the homogeneity of the protective film is reduced, and as a result, the heat resistance of the final magnetic powder may be reduced. A slurry temperature of 15°C to 25°C is more preferably preferred.
[0085] [Second washing process]
[0086] Next, the slurry containing nitride particles after the pickling process undergoes a water washing treatment (second water washing process). During the pickling process, the nitride particles in the slurry are acid-washed. At this time, byproducts (such as Ca(OH)₂) and heterogeneous phases (such as rare earth enriched phases) sometimes dissolve, and reducing agent ions (such as Ca ions), rare earth ions (R ions), and transition metal ions (TM ions) are generated in the slurry. Water washing is used to dilute and remove these generated ions.
[0087] There is no limitation to the water washing method. For example, a series of operations including stirring, settling, and decantation can be performed on a slurry containing nitride particles. Water can then be added as needed. From the viewpoint of thoroughly removing generated ions, it is preferable to repeat this series of operations.
[0088] Water rinsing is performed until the transition metal ions in the slurry are sufficiently removed. For example, the concentration of transition metals (TM) (such as Fe concentration) in the supernatant of the slurry before the addition of the phosphoric acid aqueous solution in the subsequent surface treatment process is reduced to preferably 1.0 g / L or less, more preferably 0.3 g / L or less.
[0089] [Surface Treatment]
[0090] Next, an aqueous phosphoric acid solution is added to the slurry containing nitride particles after the second water washing process, forming a phosphorus-containing protective film on the surface of the nitride particles (surface treatment process). By setting a phosphorus-containing protective film, the heat resistance of the final magnetic powder is improved.
[0091] In the surface treatment process, the slurry obtained in the second water washing step is re-injected with water, and a phosphoric acid aqueous solution is added while stirring the resulting post-injection slurry. By adding the phosphoric acid aqueous solution, the pH of the slurry decreases from its initial value (typically 6–9), and then increases again as the phosphates react with the nitride particles. It should be noted that the phosphoric acid aqueous solution refers specifically to an aqueous solution of phosphoric acid. Furthermore, "phosphates" encompasses both phosphoric acid and phosphates.
[0092] Because thorough water washing was performed in the previous second water washing process, the amount of transition metals in the supernatant of the slurry before the phosphoric acid aqueous solution is sufficiently reduced. Preferably, the concentration of transition metals (TM) (such as Fe concentration) in the supernatant of the nitride-containing slurry before adding the phosphoric acid aqueous solution is 1.0 g / L or less. Therefore, a protective film with excellent uniformity is formed, and the heat resistance of the final magnetic powder is further improved. In contrast, when the TM concentration is high, most of the added phosphoric acid is consumed in the formation of transition metal phosphates such as ferrous phosphate and ferric phosphate. Therefore, the formation of the protective film becomes insufficient, and the uniformity of the obtained protective film deteriorates. From the viewpoint of improving the heat resistance of the magnetic powder, the TM concentration of the slurry supernatant is more preferably 0.3 g / L or less.
[0093] Examples of phosphoric acid aqueous solutions include one or more phosphoric acids (phosphoric acid, phosphates), such as orthophosphoric acid, disodium hydrogen phosphate, and sodium dihydrogen phosphate. Only one type of phosphoric acid may be used, or multiple types of phosphoric acids may be used in combination.
[0094] Preferably, the amount of phosphoric acid aqueous solution added in the surface treatment process, expressed as phosphorus (P), is 0.03% by mass or more and 1.0% by mass or less relative to the magnetic powder. In other words, the amount of phosphorus (P) contained in the added phosphoric acid aqueous solution is 0.03% by mass or more and 1.0% by mass or less relative to the magnetic powder. By controlling the amount of P within this range, magnetic powder with high magnetic properties and excellent heat resistance can be obtained. In contrast, when the amount of P is less than 0.03% by mass, the formation of the protective film and the resulting improvement in the heat resistance of the magnetic powder are insufficient. When the amount of P exceeds 1.0% by mass, the amount of excess phosphoric acid is too large, and the magnetic properties of the final magnetic powder, such as the maximum magnetic polarization, decrease. From the viewpoint of improving magnetic properties and heat resistance, the amount of phosphoric acid aqueous solution, expressed as P, is more preferably 0.07% by mass or more and 0.8% by mass or less relative to the magnetic powder.
[0095] Preferably, in the surface treatment process, the temperature of the slurry containing nitride particles is maintained between 13°C and 30°C. When the slurry temperature is below 13°C, the reaction between the added phosphate and the nitride particles cannot proceed sufficiently, making it difficult to form a protective film with excellent uniformity. When the slurry temperature exceeds 30°C, the reaction between the phosphate and the nitride particles proceeds excessively. Therefore, the thickness deviation of the protective film becomes larger, and as a result, the effect of improving heat resistance may become insufficient. In addition, strong etching marks may be generated on the surface of the nitride particles, and magnetic properties sensitive to the particle surface structure, such as coercivity, may decrease. From the viewpoint of improving the magnetic properties and heat resistance of the magnetic powder, the slurry temperature is more preferably between 16°C and 25°C.
[0096] [Third washing process]
[0097] Next, the slurry containing nitride particles after the surface treatment process is subjected to water washing to obtain a wet-treated product (third water washing process). During the surface treatment process, transition metal phosphates, rare earth phosphates, or their complex salts sometimes form byproducts outside the protective coating. For example, when phosphates react with nitride particles, phosphate particles such as ferrous phosphate and ferric phosphate may sometimes form byproducts. Water washing removes these byproducts (phosphate particles).
[0098] There is no limitation to the water washing method. For example, a series of operations including stirring, settling, and decantation can be performed on a slurry containing nitride particles. Water can be added as needed. From the viewpoint of thoroughly removing byproducts, it is preferable to repeat the series of operations.
[0099] The concentration, temperature, and number of decantations of the slurry in the third washing step are not limited. However, it is preferable that the phosphorus (P) concentration in the slurry is low at the end of the third washing step. Specifically, it is preferable to perform water washing treatment until the phosphorus (P) concentration in the supernatant of the slurry is below 100 mg / L. If the P concentration is too high, the magnetic properties of the final magnetic powder, such as the maximum magnetic polarization, may decrease. From the viewpoint of improving magnetic properties, the P concentration in the supernatant is more preferably below 50 mg / L.
[0100] <Drying Process>
[0101] As needed, a drying process (drying process) can be included to dry the wet-processed material (nitride particles) after washing. The drying method is not limited. For example, a filter cake containing magnetic powder can be obtained by dewatering a slurry containing the wet-processed material, and then the filter cake can be dried. Dewatering can be performed using known solid-liquid separation equipment such as a Nutsche filter, a filter press, and / or a centrifuge. Drying can be performed under reduced pressure or by heating. To improve drying efficiency, the filter cake can be stirred during drying. Furthermore, to further improve drying efficiency, the solvent in the slurry before dewatering can be replaced. For example, the water in the slurry can be replaced with alcohols such as methanol, ethanol, and / or propanol.
[0102] <Pulverizing Process>
[0103] As needed, a step (pulverization step) can be included to pulverize the wet-treated material (nitride particles) after washing or drying. The pulverization method is not limited; it can be performed wet or dry. In the case of wet pulverization, pulverization in an organic solvent is preferred. In the case of dry pulverization, pulverization in a non-reactive environment is preferred. Furthermore, a surface treatment to impart weather resistance can be applied simultaneously with or after pulverization to the treated material.
[0104] This process is repeated to produce the magnetic powder of this embodiment. That is, the wet-processed material after wet treatment, drying, and / or pulverization can be used as the magnetic powder. The average particle size D50 of the manufactured magnetic powder is typically 1 μm or more and 10 μm or less, preferably 1 μm or more and 5 μm or less, and more preferably 1 μm or more and 3 μm or less.
[0105] 2. Rare Earth Transition Metal Nitrogen-Based Magnetic Powders
[0106] The rare-earth transition metal magnetic powder of this embodiment contains at least a rare-earth metal (R), a transition metal (TM), and nitrogen (N) as its main components. Details of the rare-earth metal (R) are as described above. While not limited, examples of rare-earth metals include one or more selected from the group consisting of yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), and ytterbium (Yb). Sm is particularly preferred. Furthermore, Sm can be used in combination with other rare-earth metals besides Sm, such as La and / or Ce. For example, 70 atomic percent or more of the rare-earth metal can be Sm, and less than 30 atomic percent can be composed of other elements (La, Ce, etc.).
[0107] Details regarding transition metals (TM) are also as described above. While not limited, examples of transition metals include one or more selected from the group consisting of iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), chromium (Cr), manganese (Mn), zinc (Zn), molybdenum (Mo), and tungsten (W). However, Fe is particularly preferred. Furthermore, Fe can be used in combination with at least one other transition metal besides Fe, for example, selected from the group consisting of Cr, Mn, Co, and Ni. For example, 90 atomic percent or more of the transition metal can be Fe, and less than 10 atomic percent can be composed of other elements (Cr, Mn, Co, Ni, etc.).
[0108] The magnetic powder in this embodiment has Th2Zn 17 Type, Th2Ni 17 Any crystal structure of type TbCu7 and type TbCu7. Examples of magnetic powders with such crystal structures include those with Sm2Fe... 17 N3 represents the basic composition of the powder (Sm2Fe). 17 N3 series powder). Sm2Fe 17 Nitrogen-based powders exhibit excellent magnetic properties and are useful as bonding magnet materials. It should be noted that the magnetic powder of this embodiment is not limited to having a stoichiometric composition. Deviations in composition are permissible as long as the crystal structure is maintained and the R / TM ratio requirement described later is met.
[0109] The average atomic ratio (R / TM ratio) of the rare earth metal (R) to the transition metal (TM) in the magnetic powder of this embodiment is 0.107 or more and 0.121 or less. The average value of the R / TM ratio is evaluated by the method described later.
[0110] The average R / TM ratio serves as a benchmark for the main phase composition of magnetic powder. By controlling the average value within the aforementioned range, the main phase composition of the magnetic powder is optimized, resulting in improved magnetic properties. Conversely, if the average value is less than 0.107, there is an excess of transition metals in the magnetic powder. The transition metal enrichment phases, which are heterogeneous phases such as α-Fe and Fe nitrides, cannot be suppressed. Therefore, the magnetic properties of the magnetic powder, such as maximum magnetic polarization and coercivity, decrease. On the other hand, when the average value exceeds 0.121, there is an excess of rare earth metals. Since the rare earth enrichment phases, which are heterogeneous phases such as SmFe5, SmFe3, and / or SmFe2, cannot be suppressed, the magnetic properties decrease. From the viewpoint of improving magnetic properties, the average R / TM ratio is preferably 0.108 or higher and 0.118 or lower.
[0111] It should be noted that the average R / TM ratio was calculated as follows. First, a thermosetting resin was mixed with magnetic powder, and the resulting mixture was pressed into shape and then thermoset to create a compression mold. Then, the cross-section of the compression mold was exposed by grinding to create a sample for scanning electron microscopy (SEM). The ground cross-section of the prepared SEM sample was observed using a scanning electron microscope (SEM) at a magnification of at least 1000 particles entering the field of view. Energy dispersive X-ray spectroscopy (EDS) analysis of the entire field of view was performed using the standardless fundamental parameter method to determine the R / TM atomic ratio.
[0112] In this embodiment, the area proportion of rare earth-enriched phases, in the cross-section of the magnetic powder whose atomic ratio (R / TM) of rare earth metals (R) to transition metals (TM) exceeds 0.130, is 1.0% or less. The area proportion of rare earth-enriched phases is evaluated by a method described later.
[0113] As described above, the average R / TM ratio of the magnetic powder as the main phase composition in this embodiment is limited to a specified range. However, when observed locally, compositional deviations sometimes occur. In particular, magnetic powders containing rare earth elements and transition metals as main constituent elements often contain rare earth-enriched heterogeneous phases (SmFe5, SmFe3, SmFe2, etc.) due to insufficient element diffusion, heterogeneous phase formation, and various reasons caused by manufacturing conditions. Such rare earth-enriched phases are a cause of reduced magnetic properties, and therefore are excluded as much as possible in this embodiment. The area ratio of rare earth-enriched phases is preferably 0.8% or less, more preferably 0.5% or less. There is no limitation on the lower limit of the area ratio. For example, it can be 0.1% or more, 0.3% or more, or 0.5% or more.
[0114] It should be noted that the area ratio of the rare earth-enriched phase is calculated as follows. SEM observation is performed on the ground cross-section of the sample used for SEM observation, yielding a reflected electron image. Image analysis utilizing contrast differences is performed on the obtained reflected electron image to determine the area ratio of the rare earth-enriched phase. That is, relative to the main phase region of the magnetic powder, the rare earth-enriched phase region contains a large amount of high-mass rare earth metals and therefore appears brightly in the reflected electron image. Therefore, if the area ratio of the brightly displayed region in the reflected electron image is determined, the area ratio of the rare earth-enriched phase can be calculated. Specifically, in the reflected electron image, a contrast threshold is set to detect only the rare earth-enriched phase region (regions with an R / TM atomic ratio exceeding 0.130), and the reflected electron image is binarized. Then, the area of the rare earth-enriched phase is calculated using the binarized reflected electron image, and divided by the area of the entire particle cross-section of the field of view, thereby determining the area ratio of the rare earth-enriched phase.
[0115] The magnetic powder of this embodiment has the effect of stably possessing a high maximum magnetic polarization. The maximum magnetic polarization Jm is preferably 1.33T or more, and more preferably 1.40T or more.
[0116] The magnetic powder of this embodiment has a protective film with excellent uniformity. Therefore, it has excellent heat resistance. The heat resistance can be evaluated by the retention rate of coercivity [HcJ(1000) / HcJ(0)], which is the ratio of the coercivity after heating (HcJ(1000) to the coercivity before heating HcJ(0)) after heating in the atmosphere at 150°C for 1000 hours. The retention rate of coercivity [HcJ(1000) / HcJ(0)] is preferably 83% or more, more preferably 87% or more.
[0117] Example
[0118] The invention is described in more detail using the following examples and comparative examples. However, the invention is not limited to the following examples.
[0119] (1) Evaluation of magnetic powder
[0120] The magnetic powders prepared in the examples and comparative examples were evaluated for various properties as follows.
[0121] <Particle size>
[0122] The particle size of magnetic powder was evaluated using an airflow dispersion laser diffraction particle size distribution measuring device, and the cumulative 50% diameter in the particle size distribution based on volume was determined as D50.
[0123] <R / Fe atomic ratio>
[0124] The composition (R / Fe ratio) of the magnetic powder was determined by scanning electron microscopy (SEM). Specifically, a thermosetting resin was mixed with the magnetic powder, and the resulting mixture was pressed into shape and then thermoset to produce a compression molded body. The amount of thermosetting resin mixed was adjusted to 4–5% by mass relative to the magnetic powder. Then, the cross-section of the compression molded body was exposed by grinding to prepare a sample for SEM observation.
[0125] Then, the ground cross-section of the sample for SEM observation was observed using a scanning electron microscope (SEM; JST-IT200, Nippon Electron Ltd.). Observations were performed at 1000x magnification, with three positions within a field of view approximately 100 μm square. Each field of view contained more than 5000 particles. EDS analysis was then performed on the entire field of view using the standard-free basic parameter method to determine the R / Fe atomic ratio. The analysis was performed at an accelerating voltage of 25 kV.
[0126] <Area proportion of rare earth enriched phases>
[0127] The area ratio of rare-earth enriched phases was determined by SEM observation. Specifically, SEM observation was performed on a ground cross-section of the sample prepared for SEM observation to determine the R / Fe atomic ratio. Observation was conducted at 1000x magnification, and electron reflection images were captured in a field of view approximately 100 μm square. Each field of view contained more than 5000 particles. Then, image analysis was performed on the obtained electron reflection images using contrast differences. Specifically, the contrast threshold was set to detect only the rare-earth enriched phase region (regions with an R / Fe atomic ratio exceeding 0.13), and the electron reflection image was binarized. The area *s* of the rare-earth enriched phase was then determined from the binarized electron reflection image. Next, the contrast threshold was changed to include both the rare-earth enriched phase region and the main phase region, and the electron reflection image was binarized again. The total area *S* of the particles was then determined from the binarized electron reflection image. The area ratio of rare earth enriched phases can be obtained by dividing the area s by the area S.
[0128] <Magnetic properties>
[0129] The magnetic properties of the magnetic powder were determined according to the Japan Association for Adhesive Magnetic Industries, Guidelines for Adhesive Magnetic Testing Methods, BM-2002, BM-2005. An orientation magnetic field of 1600 kA / m was applied to prepare a sample in stearic acid to orient the magnetic powder. After magnetization with a magnetic field of 4.0 MA / m, the specific gravity of the magnetic powder was set to 7.67 g / cm³. 3 Using a vibrating sample magnetometer with a maximum magnetic field of 1.6 MA / m, the maximum magnetic polarization Jm (T), coercivity HcJ (MA / m), and rectangularity Hk (MA / m) were measured. Here, rectangularity Hk (MA / m) is the magnetic field H at the point in the second quadrant of the magnetization curve where the magnetic polarization J decreases to 90% of the residual magnetic polarization Jr.
[0130] <Heat resistance>
[0131] Magnetic powder was heated in the atmosphere at 150°C for 1000 hours, and the coercivity before heating (HcJ(0)) and after heating (HcJ(1000)) were measured. The coercivity was measured by the same method as the magnetic properties described above. Then, as an index for evaluating heat resistance, the ratio of the coercivity after heating (HcJ(1000)) to the coercivity before heating (HcJ(0)) [HcJ(1000) / HcJ(0)] was calculated as the coercivity retention rate.
[0132] <Thermogravimetric Determination>
[0133] Thermogravimetric analysis (TG) of the magnetic powder was performed. The determination was carried out as follows: the sample was heated at a rate of 20 °C / min while dry air (N2-21% O2) was circulated at a flow rate of 100 mL / min.
[0134] (2) Preparation and evaluation results of magnetic powder
[0135] [Example 1]
[0136] <Reduction and Diffusion Process>
[0137] Average particle size D 50 624g of samarium oxide powder with a thickness of 2.3μm, D 50 1553 g of 40 μm iron powder and 248 g of granular metallic calcium were mixed in a mixer to obtain a mixture with an R / Fe atomic ratio (Sm / Fe atomic ratio) of 0.129. The mixture was placed in an iron crucible and heated at 1150 °C for 6 hours under argon atmosphere to obtain the reaction product (reduction-diffusion treated product).
[0138] <Hydrogen Crushing Process>
[0139] After cooling, the container is evacuated, and then hydrogen is supplied while adjusting the flow rate to keep the gauge pressure at +20 kPa. The reaction products are disintegrated through the hydrogen adsorption reaction.
[0140] <Nitriding process>
[0141] The reaction products (crushed material) after hydrogen treatment were fed into a tubular furnace. The process of reducing the pressure to 10 kPa and then restoring it to atmospheric pressure with nitrogen was repeated twice. Then, a mixture of ammonia (flow rate: 280 mL / min) and hydrogen (flow rate: 90 mL / min) was passed through the furnace while the temperature was increased, and the furnace was heat-treated at 430°C for 9 hours. Further heat treatment was then carried out while passing hydrogen (flow rate: 1000 mL / min) for 1 hour, followed by further heat treatment while passing nitrogen (flow rate: 1000 mL / min) for 1 hour.
[0142] <Wet Processing Procedure>
[0143] 1360g of the cooled and recovered nitriding product (nitride) was added to 4L of water for slurry preparation. This process of adding water, stirring, settling, and decanting was repeated seven times (first water washing step). The calcium concentration of the final supernatant was 0.02g / L. Water was added again, and acetic acid was added while stirring the slurry at 22°C for acid washing (acid washing step). With the addition of acetic acid, the pH of the slurry decreased from 11 to 4-5. Stirring continued after the acetic acid addition was completed, and the process was stopped when the pH of the slurry exceeded 7. Then, the supernatant was drained, and the process of adding water, stirring, settling, and decanting was repeated until the Fe concentration of the supernatant was below 1.0g / L (second water washing step).
[0144] Next, for surface treatment, 4L of water was added and stirred again. The Fe concentration of the supernatant was 0.1g / L, and the slurry temperature was 20°C. While stirring the slurry, a 25% by mass aqueous solution of orthophosphoric acid containing 0.31% by mass of P (based on the mass of the magnetic powder) was added (surface treatment step). By adding the orthophosphoric acid aqueous solution, the pH of the slurry decreased from 8 to 4.1, and then rose to 7 before stirring was stopped and decantation was performed.
[0145] Next, water is injected again, and the process of water injection, stirring, settling-decanting (the third water washing process) is repeated twice. At this point, the phosphorus concentration of the final slurry supernatant is 40 mg / L.
[0146] <Drying Process>
[0147] After the final decantation following the third water washing process, 1 L of 2-propanol was added and stirred, followed by vacuum filtration to obtain a filter cake. The obtained filter cake was dried under reduced pressure at 130°C with stirring in a mixer, and then cooled to obtain samarium-iron-nitrogen alloy powder. In the obtained alloy powder, D... 50 The particle size is 21 μm, the Sm composition is 23.1% by mass, and the P composition is 0.15% by mass.
[0148] <Pulverizing Process>
[0149] 900g of the obtained samarium iron nitrogen alloy powder was micronized using a media stirring mill. Here, 2-propanol with 85% aqueous solution of orthophosphoric acid was used as the pulverizing solvent. The pulverized slurry was heated and dried under reduced pressure to obtain magnetic powder. The manufacturing conditions of Example 1 are summarized in Table 1 below.
[0150] The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder has Th2Zn 17 Type D crystal structure 50 The thickness is 2.1 μm. Furthermore, the magnetic properties are: Jm (maximum magnetic polarization): 1.42 T, HcJ (coercivity): 0.90 MA / m, Hk (rectangularity): 0.52 MA / m. The phosphorus composition of the magnetic powder is 0.52% by mass.
[0151] A compressed molded body was fabricated from the obtained magnetic powder, and SEM images of three arbitrary locations on its ground cross-section were performed at 1000x magnification. The resulting SEM reflected electron images are shown below. Figures 1-3 EDS analysis was performed on the entire 100 μm square region for Sm and Fe, and the R / Fe atomic ratios (Sm / Fe atomic ratio; R / TM atomic ratio) were calculated. The results showed that the respective R / Fe atomic ratios were 0.113, 0.113, and 0.114, and the average value (average R / Fe atomic ratio) was 0.113.
[0152] On the other hand, in each of the respective images, for any bright contrast particles, EDS analysis was performed at several points to determine the R / Fe atomic ratio (Sm / Fe atomic ratio; R / TM atomic ratio), and the results were all values exceeding 0.13. Therefore, through image analysis, the ratio of the cross-sectional area of these bright contrast particles to the total particle cross-sectional area was calculated. Their respective area proportions were 0.5%, 0.4%, and 0.5%, with an average (area proportion of rare earth enriched phases) of 0.5%.
[0153] The magnetic powder was heated at 150°C for 1000 hours in the atmosphere. After heating, it was removed and the coercivity HcJ(1000) at room temperature was evaluated, which was 0.77 MA / m. The coercivity retention rate [HcJ(1000) / HcJ(0)], which is an indicator of heat resistance, was calculated and found to be 86%.
[0154] [Example 2~Example 4]
[0155] The manufacturing conditions were changed as shown in Table 1 below. Otherwise, the magnetic powder was prepared following the same procedures as in Example 1. The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder exhibits Th₂Zn content. 17 Type crystal structure.
[0156] [Example 5]
[0157] Compared to D obtained by reduction diffusion method 50 Sm2Fe with a diameter of 30 μm 17 2 kg of alloy powder was mixed with 200 g of samarium oxide powder using a mixer. This mixed powder was then pulverized using a media-stirred pulverizer with a solvent of 4.4 kg of 2-propanol and 46 g of 85% phosphoric acid until D was achieved. 50 The particle size was reduced to 1.4 μm. The resulting slurry was heated to 210 °C while being subjected to reduced pressure using a mixer. Once the vacuum level was confirmed to have decreased due to gas release and the vacuum level had risen sufficiently, the slurry was cooled.
[0158] The resulting pulverized mixture, 2.00 kg (from Sm2Fe), was processed in this manner.17 In a mixture consisting of 1.82 kg of alloy powder and 0.18 kg of samarium oxide, 466 g of granular metallic calcium was added as a reducing agent, and the mixture was stirred in an argon atmosphere. This reducing agent dosage was 2.5 times the reduction requirement (equivalent) calculated from the oxygen analysis value of the pulverized mixture. The resulting raw material mixture had an R / Fe atomic ratio of 0.160.
[0159] As part of the reduction-diffusion process, the raw material mixture is placed in an iron crucible and heated under argon atmosphere. After maintaining the temperature at 830°C for 2 hours, it is cooled (reduction-diffusion treatment process). Next, the reaction product recovered from the crucible (reduction-diffusion treated product) is crushed by hydrogen absorption (hydrogen treatment) and then subjected to nitriding treatment. In the hydrogen treatment, the reaction product (reduction-diffusion treated product) is placed in a tubular furnace, the furnace pressure is reduced to -100 kPa, and then hydrogen is introduced to atmospheric pressure while the temperature is raised to 300°C. Since the reaction product absorbs hydrogen while heating, the exhaust valve of the tubular furnace is closed while the furnace continues to supply hydrogen during the period when negative pressure is achieved. Cooling is then performed after heating and hydrogen absorption are completed (hydrogen crushing process). The reaction product (crushed product) after hydrogen treatment is in a crushed state. Next, in order to carry out the nitriding treatment, the pressure inside the tubular furnace was reduced to 5 kPa absolute pressure, and nitrogen gas was introduced to atmospheric pressure. Then, the nitrogen flow rate was directly set to 1 L / min for heating, and the temperature was maintained at 450°C for 24 hours before cooling. This yields the nitriding reaction product (nitride) (nitriding process).
[0160] Next, as a wet treatment step, 2.0 kg of the nitriding reaction product (nitride) was added to 4 L of water for slurry preparation. This process of adding water, stirring, settling, and decanting was repeated 10 times (first water washing step). The calcium concentration of the final supernatant was 0.1 g / L. Water was added again, and acetic acid was added while stirring the slurry at 13°C for acid washing (acid washing step). With the addition of acetic acid, the pH of the slurry decreased from 12 to about 5. Stirring continued after the acetic acid addition was completed, and the process was stopped when the pH of the slurry exceeded 7. Then, the supernatant was drained, and the process of adding water, stirring, settling, and decanting was repeated until the Fe concentration of the supernatant was below 1.0 g / L (second water washing step).
[0161] Next, 4L of water was added again, and the mixture was stirred. The Fe concentration of the supernatant was 0.9g / L, and the slurry temperature was 13℃. While stirring the slurry, a 25% by mass aqueous solution of orthophosphoric acid containing 1.0% by mass of P (based on the mass of the magnetic alloy powder) was added (surface treatment step). By adding the orthophosphoric acid aqueous solution, the pH of the slurry decreased from 8 to 3.3, and then rose to 7. Stirring was stopped, and decantation was performed. Then, water was added again, and the process of adding water, stirring, settling, and decantation was repeated 8 times (third water washing step). At this point, the P concentration of the final slurry supernatant was 20mg / L.
[0162] After the final decantation in the third water washing process, 2L of 2-propanol was added and stirred. The filter cake obtained by suction filtration was dried under reduced pressure at 170°C using a mixer, and then cooled to obtain samarium iron nitrogen alloy powder (drying process). The D of the obtained alloy powder... 50 The particle size is 2.9 μm. Furthermore, the Sm composition is 23.8% by mass, and the P composition is 0.83% by mass. The alloy powder was micronized in a 2-propanol solvent containing an aqueous solution of orthophosphoric acid using 0.2 mm alumina balls, and the slurry was dried to obtain magnetic powder (pulverization process).
[0163] The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder has Th2Zn 17 Type D crystal structure 50 The thickness is 1.3 μm. Furthermore, it exhibits magnetic properties of Jm (maximum magnetic polarization): 1.13 T, HcJ (coercivity): 1.44 MA / m, and Hk (rectangularity): 0.40 MA / m. Additionally, the P composition is 0.83% by mass.
[0164] For the ground cross-section of the compressed molded body made from the obtained magnetic powder, the R / Fe atomic ratio (Sm / Fe atomic ratio; R / TM atomic ratio) was calculated, and the average result was 0.121. Furthermore, the average proportion of regions with an R / Fe atomic ratio exceeding 0.13 (area proportion of rare earth enriched phases) obtained by EDS analysis was 0.8%. Further, the coercivity retention rate of the magnetic powder [HcJ(1000) / HcJ(0)] was 91%.
[0165] [Example 6]
[0166] The manufacturing conditions were changed as shown in Table 1 below. Otherwise, the magnetic powder was prepared using the same steps as in Example 5. The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder exhibits Th₂Zn content. 17 Type crystal structure.
[0167] [Example 7]
[0168] The manufacturing conditions were modified as shown in Table 1 below. Furthermore, the raw materials were weighed using the same steps as in Example 1, and a reduction-diffusion process and a hydrogen-breaking process were performed. Next, a wet treatment process and a drying process were performed before the nitriding process to obtain samarium-iron alloy powder.
[0169] Then, as a nitriding process, the samarium-iron alloy powder was placed in a tubular furnace, and the temperature was increased while a mixed gas of ammonia (flow rate: 280 mL / min) and hydrogen (flow rate: 90 mL / min) was passed through it, and the powder was heat-treated at 430°C for 9 hours. Further heat treatment was carried out while passing hydrogen (flow rate: 1000 mL / min) for 1 hour, followed by further heat treatment while passing nitrogen (flow rate: 1000 mL / min) for 1 hour, yielding samarium-iron nitrogen-based alloy powder.
[0170] The obtained alloy powder was micronized in 2-propanol solvent with added orthophosphoric acid solution, just like in Example 1, and then dried into a slurry to obtain magnetic powder.
[0171] The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder has Th2Zn 17 Type D crystal structure 50 The thickness is 2.1 μm. Additionally, the magnetic properties are: Jm: 1.41 T, HcJ: 0.86 MA / m, Hk: 0.39 MA / m. Furthermore, the P composition is 0.49% by mass.
[0172] Compressed bodies were fabricated from the obtained magnetic powder, and SEM images of three arbitrary locations on the ground cross-section were performed at 1000x magnification. The resulting SEM reflected electron images are shown in Figures 4-6. Similar to Example 1, the R / Fe atomic ratio (Sm / Fe atomic ratio; R / TM atomic ratio) of the ground cross-section was calculated, with an average value of 0.117. Furthermore, EDS analysis showed that the area proportion (area proportion of rare earth enriched phases) of regions with an R / Fe atomic ratio exceeding 0.13 was 2.2%. Additionally, the coercivity retention rate of this magnetic powder was 85%.
[0173] [Example 8]
[0174] The second water washing process proceeds from the reduction-diffusion process to the wet treatment process under the conditions shown in Table 1 below. During the final rinse of the second water washing process, when the Fe concentration in the supernatant is below 1 g / L, a drying process is performed to recover the samarium-iron-nitrogen alloy powder without a surface treatment process or a third water washing process. The alloy powder recovered through this stage is not surface treated.
[0175] The obtained alloy powder was micronized in 2-propanol solvent with added orthophosphoric acid solution, as in Example 1, and then dried into a slurry to obtain magnetic powder.
[0176] The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder has Th2Zn 17 Type D crystal structure 50 The thickness is 2.1 μm. Additionally, the magnetic properties are Jm: 1.44 T, HcJ: 0.93 MA / m, Hk: 0.55 MA / m. Furthermore, the P composition is 0.43% by mass.
[0177] [Example 9~Example 15]
[0178] The manufacturing conditions were changed as shown in Table 1 below. Otherwise, the magnetic powder was produced using the same procedures as in Example 1. The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder exhibits Th₂Zn content. 17 Type crystal structure.
[0179] [Example 16]
[0180] In the nitriding process, the reaction product after hydrogen treatment was placed into a tubular furnace. The pressure was then reduced to 10 kPa absolute twice to restore the pressure of the 4:1 ammonia and hydrogen mixture to atmospheric pressure. Then, while circulating a mixture of ammonia (flow rate: 280 mL / min) and hydrogen (flow rate: 90 mL / min), the temperature was increased, and the mixture was heat-treated at 430°C for 9 hours. Otherwise, magnetic powder was prepared using the same procedures as in Example 1.
[0181] The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder has Th2Zn 17 Type crystal structure.
[0182] [Example 17]
[0183] In the nitriding process, the reaction product after hydrogen treatment was placed in a tubular furnace, and then the pressure was reduced to 80 kPa absolute before being restored to atmospheric pressure with nitrogen. Then, a mixture of ammonia (flow rate: 280 mL / min) and hydrogen (flow rate: 90 mL / min) was passed through while the temperature was increased, and the mixture was heat-treated at 430°C for 9 hours. Otherwise, magnetic powder was prepared using the same procedures as in Example 1.
[0184] The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder has Th2Zn 17 Type crystal structure.
[0185] [Example 18]
[0186] The manufacturing conditions were changed as shown in Table 1 below. Otherwise, the magnetic powder was prepared using the same procedures as in Example 5. The evaluation results of the obtained magnetic powder are shown in Table 2 below. The magnetic powder exhibits Th₂Zn content. 17 Type crystal structure.
[0187] [Table 1]
[0188] [Table 2]
[0189] (3) Summary of evaluation results
[0190] Examples 1-4 are magnetic powders prepared from a mixture containing samarium oxide, iron powder (metallic iron powder), and metallic calcium. In these magnetic powders, the R / Fe atomic ratio (R / TM atomic ratio) is 0.108-0.114, and the proportion of impurity phases (rare earth enriched phases) (0.5-0.7%) is less than 1.0%. Therefore, the maximum magnetic polarization Jm is as high as 1.33-1.42 T. Furthermore, in these magnetic powders, the retention rate of coercivity [HcJ(1000) / HcJ(0)], an indicator of heat resistance, is 83-88%.
[0191] In contrast, in Example 7, where the nitriding and wet treatment processes were replaced in sequence, the R / Fe atomic ratio (0.123) exceeded 0.121. Furthermore, the proportion of impurity phases (rare earth enriched phases) (2.2%) exceeded 1.0%. Therefore, the maximum magnetic polarization Jm (1.40T) was lower than that of Example 1 (1.42T), which had the same D50 (2.1μm). Additionally, the rectangularity Hk (0.39MA / m) was also lower than that of Example 1 (0.52MA / m).
[0192] In Example 8, where the surface treatment step and the third water washing step in the wet treatment process were omitted, Jm reached as high as 1.44T, but the coercivity retention rate was as low as 68%.
[0193] The alloy powders of Examples 1 and 8 (after the drying process, D) 50 The thermogravimetric analysis (TG) results obtained for the samarium-iron-nitrogen alloy before and after 20 μm are shown in Figure 7. These results indicate that the alloy powder undergoes an oxidation increment upon heating in air. The temperature at which the oxidation increment becomes 1% by heating is 410 °C in Example 8, compared to 570 °C in Example 1 where a protective coating was applied. It is speculated that the poor heat resistance (oxidation resistance) of the alloy powder before pulverization leads to poor uniformity of the protective coating on the magnetic alloy powder pulverized while undergoing the surface treatment described in Patent Document 3, thus resulting in poor heat resistance of the magnetic powder.
[0194] Example 9 shows the results when the R / Fe atomic ratio (0.116) of the raw material mixture is less than 0.117, and Example 10 shows the results when the R / Fe atomic ratio (0.163) of the raw material mixture is greater than 0.160. In the former, the R / Fe atomic ratio (0.106) of the magnetic powder obtained after the pulverization process is less than 0.107, and the coercivity HcJ is as low as 0.73 MA / m. In the latter, the R / Fe atomic ratio (0.122) of the similarly pulverized magnetic powder is greater than 0.121, and the proportion of impurity phase (rare earth enriched phase) (4.9%) exceeds 1.0%. Therefore, Jm is as low as 1.17T, and HcJ is as low as 0.81 MA / m. The retention rates of coercivity are as low as 82% and 78%, respectively.
[0195] Example 11 shows the results when the processing temperature (1210°C) in the reduction-diffusion process is higher than 1200°C. Due to the high-temperature treatment causing particle sintering, sintered particles were observed in the magnetic powder obtained after the drying process. Therefore, the magnetic powder obtained after the pulverization process had a Jm as low as 1.25T, a Hk as low as 0.33 MA / m, and a coercivity retention rate as low as 79%.
[0196] Example 12 shows the results when the slurry temperature in the fourth acid cleaning process is high, and the R / Fe atomic ratio (0.106) of the magnetic powder obtained after the pulverization process is lower than 0.107. In contrast, Example 13 shows the results when the slurry temperature in the acid cleaning process is low, resulting in less dissolution of the secondary phases during acid cleaning, and an R / Fe atomic ratio (0.122) higher than 0.121. The former, due to excessive acid cleaning, resulted in an R / Fe atomic ratio (0.106) of the magnetic powder obtained after the pulverization process lower than 0.107. Furthermore, HcJ was as low as 0.76 MA / m. On the other hand, the latter's magnetic powder had an R / Fe atomic ratio (0.122) higher than 0.121, and the proportion of impurity phases (rare earth enriched phases) (1.8%) exceeded 1.0%. Therefore, the Jm of the magnetic powder was as low as 1.21 T. Furthermore, the retention rates of coercivity were as low as 74% and 77%, respectively.
[0197] Example 14 shows the results when the amount of phosphoric acid (P) in the phosphoric acid aqueous solution added during the surface treatment process is less than 0.03% by mass (0.02% by mass relative to the alloy powder). In contrast, Example 15 shows the results when the amount of phosphoric acid (P) is greater than 1.0% by mass (1.2% by mass relative to the alloy powder). The former has a Jm of 1.28T, which is not particularly low. However, the retention rate of coercivity is as low as 72%. On the other hand, the latter has a Jm of 1.19T as low as the original due to the addition of excessive phosphoric acid aqueous solution.
[0198] Example 16 illustrates the results of nitriding after the hydrogen-treated reaction product was introduced into a tubular furnace, the pressure was reduced to 10 kPa, and the pressure was restored to atmospheric pressure using a gas mixture of ammonia and hydrogen in a 4:1 ratio. This process was repeated twice. Because the gas used to restore the pressure contained hydrogen, residual hydrogen remained in the pores and cracks of the reaction product, hindering the diffusion of the nitriding gas during nitriding and resulting in an increase in the amount of nitrogen-free phase. Consequently, the proportion of impurity phases (rare earth enriched phases) (2.1%) exceeded 1.0%, and the Jm, HcJ, and Hk of the magnetic powder were all lower than in Example 1. The coercivity retention rate was also as low as 81%.
[0199] Example 17 shows the result of nitriding after depressurization to an absolute pressure of 80 kPa, restoration to atmospheric pressure with nitrogen, and subsequent single-stage nitriding. Because the environment (80 kPa) of the fragmented material was not sufficiently depressurized, similar to Example 16, residual hydrogen remained in the pores and cracks of the reaction products, hindering the diffusion of the nitriding gas during nitriding and resulting in an increase in the amount of nitrogen-free phase. Consequently, the proportion of impurity phases (rare earth enriched phases) exceeded 1.0% (2.6%), and the Jm, HcJ, and Hk of the magnetic powder were all lower than in Example 1. The retention rate of coercivity was also low, at only 78%.
[0200] Examples 5 and 6 show the results obtained using a mixture containing samarium oxide, rare earth iron alloy powder, and metallic calcium as raw materials, with reduction diffusion treatment temperatures set to 830°C and 930°C, respectively. Jm ranged from 1.13 to 1.20 T, and the retention rates of coercivity were 91% and 93%, respectively.
[0201] In contrast, Example 18 is an example of using a mixture of the same composition and undergoing reduction diffusion treatment at a temperature below 800°C (790°C). Jm is as low as 0.98T, and the retention rate of coercivity (79%) is lower than that of Examples 5 and 6.
Claims
1. A rare-earth transition metal nitrogen-based magnetic powder, comprising at least a rare-earth metal (R), a transition metal (TM), and nitrogen (N) as main components, having Th₂Zn content. 17 Type, Th2Ni 17 Any crystal structure in the TbCu7 type and TbCu7 type, wherein, In the aforementioned rare-earth transition metal nitrogen-based magnetic powder, the average atomic ratio (R / TM ratio) of rare-earth metal (R) to transition metal (TM) is 0.107 or higher and 0.121 or lower, and the area proportion of rare-earth enriched phases with an R / TM ratio exceeding 0.130 is 1.0% or lower. When heated at 150°C for 1000 hours in the atmosphere, the retention rate of the ratio of the coercivity after heating (HcJ(1000)) to the coercivity before heating (HcJ(0)) [HcJ(1000) / HcJ(0)] is more than 83%.
Citation Information
Patent Citations
Production of rare earth-transition metal-nitrogen alloy powder
JP1993148517A
Rare earthmetal-iron-nitrogen based magnetic powder and its production
JP2000038608A
Method of manufacturing high-weatherability magnet powder and product obtained thereby
JP2002124406A
Rare-earth-iron-nitrogen-base magnet powder and method for manufacturing the same
JP2007119909A
